Analysis of Savonius Rotor Performance Operating at Low Wind Speeds Using Numerical Study - Zakaria, A.; S. N. Ibrahim, M. (International Journal of Engineering and Technology, 2018)
This paper investigates the sensitivity of time step and time increment on the performance of 180-degree twist helical Savonius rotor using commercial computational fluid dynamic code based on flow-driven method. The best combination of time step and time increment was first determined by comparing simulated rotational speed with the actual rotor speed generated by wind speed of 5 m/s. Other rotational speeds at 2, 3, 4 and 6 m/s are then predicted based on this condition. The results show that time step and time increment have a significant impact on the accuracy of the predicted rotor rotational speed (RPM). A small time increment and a large time step require longer computational time but in return give closer rotor RPM to the actual experiment. On the contrary, a larger time increment with smaller time step dramatically reduced the computational time but resulted in poor rotor RPM prediction. The results also show that the closest RPM predicted by this analysis is when the time step and time increment were at 8000 and 0.0015 seconds respectively. This paper concludes that an accurate prediction of rotor rotational speed can be achieved by setting the right combination of time step and time increment.Â Â